Morphological and molecular diversity of rissoellids (Mollusca, Gastropoda, Heterobranchia) from the Northwest Pacific island of Hokkaido, Japan - Siadén, Luis E. Chira; Wakeman, Kevin C.; Webb, Stephen C.; Hasegawa, Kazunori; Kajihara, Hiroshi (Zootaxa, 2019)
This study deals with four species of marine microgastropods of the family Rissoellidae. Rissoella elatior (Golikov, Gulbin & Sirenko, 1987), R. golikovi (Gulbin, 1979), R. japonica n. sp., and Rissoella sp. 1 were collected in different locations around the island of Hokkaido, Japan. Light and scanning electron microscopy (SEM) were used to study the general morphology of the shell and radula, and a region of the mitochondrial cytochrome c oxidase subunit I (COI) gene was amplified for 26 specimens. Rissoella elatior is morphologically characterized by a highly asymmetrical radula with a deep notch encircled by 10–13 minute secondary cusps on the left dorsal margin of the central tooth. Rissoella golikovi is characterized by a skeneiform shell and possession of three teeth per row on the radula. Rissoella japonica n. sp. shows five teeth per row on the radula; central tooth higher than wide; lateral and marginal teeth narrow with an outer lateral projection at the base; all teeth presenting numerous small cusps on the cutting edge. Rissoella sp. 1 is distinguished from R. japonica n. sp. in having i) very short oral lobes, ii) a mantle with a large, black patch and whitish blotches inside, and iii) different color patterns associated with the visceral mass. Although Rissoella sp. 1 probably represents an undescribed species, additional specimens are needed to complete its description. This study represents a first molecular approach to the family Rissoellidae. Studies of traditional morphological characters indicated four species, the addition of COI data raised the count to eight potential species, suggesting the occurrence of cryptic species among rissoellids.